PENINGKATAN KEMAMPUAN MENULIS MAHASISWA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW - Saleh, Raja Jasal (Pusat Data dan Teknologi Informasi Kementerian Pendidikan Kebudayaan, Riset dan Teknologi, 2017)
AbstractThis research is aimed to know students’ writing ability of Pekanbaru Open University through jigsaw type of learning the cooperative model. The research methode used is Classroom Action Research conducted in two cycles. Research object is 22 sixth semester students of Pekanbaru Open University in 2015.2 academic years. The research data were collected by using test and non-test techniques. The first is used to obtain students’ writing ability data and the second is used to obtain lecturers’ and students’ observation data. The writing ability data is analyzed by assessing the students’ composition, i.e. ideas/topics (20%), contents (40%), enhanced spelling (20%), and writing system (20%). Every item was scored to find out the students’ individual completeness. The observation result data are analyzed qualitatively by describing any learning process of lecturers’ as well as the students’ activities. The reseach result shows that the implementation of the jigsaw type of cooperative learning model has improved the students’ writing ability of Pekanbaru Open University can be seen from the number of students completing any cycles. There are only five students completing the cycle I and 21 students completing the cycle II. The class avearage in choossing the theme/topics was 67.64, the contents was 67,50, enhanced spelling was 68,68, and writing system was 67.77. Overall average score was 67.82. However, in the second cycle there was an increase in choosing the theme/topics was 74.32, the content was 75.55, enhanced spelling was 75.79, and wrinting system was 75.14. Overall average score was 75.23Keywords: writing ability, jigsaw, cooperative learning AbstrakPenelitian ini bertujuan untuk mengetahui kemampuan menulis mahasiswa Universitas Terbuka (UT) Pekanbaru melalui penerapan model pembelajaran kooperatif tipe Jigsaw.Metode penelitian yang digunakan adalah Penelitian Tindakan Kelas yang dilaksanakan selama dua siklus. Objek penelitian ini adalah mahasiswa UT Pekanbaru Semester VI Tahun Ajaran 2015.2 yang berjumlah 22 orang. Pengumpulan data ini dilakukan teknik tes dan nontes. Teknik tes digunakan untuk memeroleh data kemampuan menulis mahasiswa, sedangkan teknik nontes digunakan untuk memperoleh data observasi dosen dan mahasiswa. Data kemampuan menulis dianalisis dengan memberikan penilaian terhadap karangan mahasiswa, yaitu ide/topik karangan (20%), isi (40%), ejaan yang disempurnakan (EYD) (20%), dan sistematika penulisan (20%). Setiap item diberikan skor untuk mengetahui ketuntasan mahasiswa secara individu. Data hasil observasi dianalisis secara kualitatif dengan mendeskripsikan setiap proses pembelajaran baik aktivitas dosen maupun aktivitas mahasiswa.Hasil penelitian ini menunjukkan bahwa penerapan model pembelajaran kooperatif tipe jigsaw dapat meningkatkan kemampuan menulis mahasiswa UT Pekanbaru dilihat dari jumlah mahasiswa yang tuntas setiap siklus. Mahasiswa yang tuntas pada siklus I sebanyak 5 orang dan pada siklus II sebanyak 21 orang. Dalam pemilihan tema/topik karangan rata-rata kelas adalah 67,64, isi atau kualitas karangan 67,50, penilaian EYD 68,68, dan sistematika penulisan 67,77. Secara keseluruhan rata-rata kelas mencapai 67,82. Namun, pada siklus II terjadi peningkatan dalam pemilihan tema/topik karangan rata-rata kelas adalah 74,32, isi atau kualitas karangan 75,55, rata-rata skor EYD 75,79, dan sistematika penulisan 75,14. Secara keseluruhan rata-rata kelas mencapai 75,23.Kata Kunci: Kemampuan menulis, jigsaw, pembelajaran kooperatif